Defining the Apply of Over the 60 Years Old to Yenimahalle and Abdullahpaşa Education and Research Health Center in 2000 - Deveci, S. Erhan; Ozan, Ahmet Tevfik; Açık, Yasemin (Fırat University, 2001)
Aim: It must be paid effort for elderly patients to benefit from the primary health care services. We took 60 and upper years old persons who applied to Yenimahalle and Abdullahpaşa Education and Research Health Center (ERHC). We aimed to make definition of elderly persons who live in our region. Materials and Methods: The application of 60 age and over years old people and the monthly study of village clinics which belong to 2000 year between 1 January – 31 December were investigated. Results: The population of 60 age and over years old people in Abdullahpaşa ERHC was 547, in Yenimahalle ERHC was 2996, the rate of region population was 5.9% and 8.8% respectively, the numbers of applied elderly patients were 1617 and 3324 respectively. Hypertension in Abdullahpaşa ERHC was 17.2%, in Yenimahalle ERHC was 21.7%, it took part in the first place. Acute respiratory tract infections, skeleto-muscle system and collagenous tissue infections were in first three places in both health center. In both sex, chronic illness were over 50% of the diagnosis cases. Referring the elderly persons to an another instituation's rate was 6.8% in Abdullahpaşa, in Yenimahalle it was 3.9%. Conclusion: The elderly persons who live in our region's ERHC take benefit highly from the primary health care services. It was determined that a high amount of applicated elderly persons had chronic illness.

Amaç: Yaşlıların birinci basamak sağlık hizmetlerinden yeterince yararlanmaları için çaba harcanmalıdır. Çalışmamızda Yenimahalle ve Abdullahpaşa Eğitim Araştırma Sağlık Ocaklarımız (EASO) polikliniklerine başvuran 60 yaş ve üzerindeki kişiler incelenerek genel olarak bölgemizdeki yaşlılara ait tanımlamaların yapılması amaçlanmıştır. Gereç ve Yöntem: 2000 yılına ait poliklinik defterlerinden 1 Ocak-31 Aralık 2000 tarihleri arası 60 yaş ve üzeri kişilerin başvuruları ve sağlık ocaklarının aylık çalışmaları incelenmiştir. Bulgular: 60 yaş ve üzeri nüfus Abdullahpaşa EASO'da 547, Yenimahalle EASO'da 2996, bölge nüfusuna oranları sırasıyla %5.9 ve %8.8, başvuran yaşlı hasta sayısı ise sırasıyla 1617 ve 3324'tür. Hipertansiyonun Abdullahpaşa EASO'da %17.2, Yenimahalle EASO'da %21.7 sıklıkla ilk sırada yer aldığı görülmektedir. Akut solunum yolu enfeksiyonları ile iskelet-kas sistemi ve bağ dokusunun diğer hastalıkları her iki sağlık ocağında da ilk üç içerisindedir. Her iki cinste de tanıların %50'den fazlasını kronik hastalıklar oluşturmaktadır. Yaşlıların diğer bir kuruma sevk oranları Abdullahpaşa'da %6.8, Yenimahalle'de ise %3.9'dur. Sonuç: EASO bölgelerimizde yaşayan yaşlıların birinci basamak sağlık hizmetlerinden yararlanma düzeyleri yüksektir. Başvuran yaşlıların büyük bir çoğunluğunun kronik hastalığa sahip olduğu saptanmıştır.
2000 YILINDA YENİMAHALLE ve ABDULLAHPAŞA EĞİTİM ARAŞTIRMA SAĞLIK OCAKLARINA YAPILAN 60 YAŞ ÜZERİ BAŞVURULARIN TANIMLANMASI